Pengembangan Ubudiyah Anak dengan Meningkatkan Kemampuan tatacara Sholat dan Wudhu yang Benar melalui Model Pengajaran Langsung - Ismatul Khusnah; Fadhil Akbar (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
This study aims to determine the level of knowledge and understanding of children in the correct practice of prayer and ablution through teaching using a direct teaching model. This research method uses a descriptive qualitative approach. The data used is primary data with data collection techniques using interviews, observation, and documentation. The conclusion of this study is the success of strengthening children's religion through the practice of ablution and prayer through activities with direct learning models.